Reocclusion of the treated vessel due to endothelial injury after mechanical thrombectomy in a patient with acute ischaemic stroke. Issue 8 (26th August 2019) - Hidaka, Masaoki; Yamaguchi, Shinya; Koyanagi, Yuya; Arakawa, Shuji
Abstract : A 92-year-old woman developed sudden consciousness disturbance, global aphasia and right hemiparesis. She had atrial fibrillation and cardioembolic stroke was diagnosed. Tissue plasminogen activator was administered, and endovascular treatment was initiated. The left middle cerebral artery was occluded and complete recanalisation was achieved after direct aspiration first-pass technique. However, MRI immediately after treatment showed reocclusion. Endovascular treatment was repeated and complete recanalisation was achieved. There was no evidence of cerebral artery dissection, but angiography soon after the second procedure revealed early reocclusion. Ozagrel, an antiplatelet agent, was administered intravenously and prevented reocclusion. Endothelial injury was speculated to have occurred during the first mechanical thrombectomy, leading to recurrent occlusion. Though the patient continued to have right hemiparesis, she recovered from her consciousness disturbance and aphasia after re-treatment.